Physical and physiological demands of elite team handball - Póvoas, Susana C A; Seabra, André F T; Ascensão, António A M R; Magalhães, José; Soares, José M C; Rebelo, António N C (Journal of strength and conditioning research, 2012)
This study aimed to analyze elite team handball physical and physiological demands during match play. Time-motion (N = 30) and heart rate (HR; N = 60) analyses were performed throughout 10 official matches. The defined locomotor categories were standing still, walking, jogging, fast running, sprinting, backwards movement, sideways medium-intensity movement, and sideways high-intensity movement, and playing actions studied were jumps, shots, stops when preceded by high-intensity activities, changes of direction and one-on-one situations. During matches, the mean distances covered were 4,370 ± 702.0 m. Around 80% of the total time was spent standing still (43.0 ± 9.27%) and walking (35.0 ± 6.94%) and only 0.4 ± 0.31% with sprinting. The most frequent high-intensity actions were stops, changes of direction, and one-on-one situations. Effective mean HR was 157 ± 18.0 b·min(-1) (82 ± 9.3% of HRmax), and total HR was 139 ± 31.9 b·min(-1) (72 ± 16.7% of HRmax). The HR, time spent in high-intensity activities, frequency of stops, changes of direction, one-on-one situations, and most intense periods of the game were higher during the first half than during the second half (p ≤ 0.05). The opposite was observed for the number of time outs and the time between each change of activity (p = 0.00). Handball is an intermittent exercise that primarily uses aerobic metabolism, interspersed by high-intensity actions that greatly tax anaerobic metabolism. Additionally, exercise intensity decreases from the first to the second half of the match, suggesting that neuromuscular fatigue may occur during the game. The training of elite handball players should comprise exercises targeting the ability to perform specific high-intensity actions throughout the game and to rapidly recover during the less intense periods.